2019
DOI: 10.1002/polb.24788
|View full text |Cite
|
Sign up to set email alerts
|

Dual entropic and enthalpic processes in the lower critical solution temperature phase separation of poly(vinyl methyl ether) aqueous solutions

Abstract: In the lower critical solution temperature phase separation of poly(vinyl methyl ether) aqueous solutions, the process corresponding to the weakening of the hydrogen bond interaction with increasing temperature is dominant and occurs over the entire concentration region of solutions and over a broad temperature range from 30 to 41°C, giving rise to the energetic enthalpic effect during phase separation, while the conformational change, that is, collapse of the swollen polymer coils, occurs only in the swelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Subsequently, similar entropic effects were also observed in another type III LCST behavior poly(vinyl methyl ether) (PVME) aqueous solutions. 39,42 In contrast to the complicate chemical structure in PNIPAM, the structure of PVME is very simple and there is only one polar oxygen ether atom in each repeating unit and can form hydrogen bond with a maximum of two water molecules. The DSC results showed that below the critical water concentration of 38.3 wt% (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, similar entropic effects were also observed in another type III LCST behavior poly(vinyl methyl ether) (PVME) aqueous solutions. 39,42 In contrast to the complicate chemical structure in PNIPAM, the structure of PVME is very simple and there is only one polar oxygen ether atom in each repeating unit and can form hydrogen bond with a maximum of two water molecules. The DSC results showed that below the critical water concentration of 38.3 wt% (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…39 Although the swelling state of polymer coils in extremely dilute solution and rather compact globule state of polymer chains in bulk state are clear for PNIPAM, it is still extremely challenging and difficult to conrm when and how the compact PNIPAM globules begin to swell with the continuous dilution of water solvent in concentrated solutions. Based on the above studies, 39,41,42 in this work, the entropic effects in the demixing enthalpy recovery behavior in different concentration regions and its implications on the conformational changes of polymer coils swelling state in aqueous PNIPAM solutions are investigated.…”
Section: Introductionmentioning
confidence: 99%